The effects of dance interventions on reducing the risk of falls in older adults: a network meta-analysis - Li, Ying; Wang, Zhaoguo; Li, Jiahao; Yang, Honghao; Fang, Zilong (Frontiers in Public Health, 2024)
ObjectiveThe efficacy of dance in reducing fall risks among older adults highlights its potential for geriatric health, but the optimal dance style remains uncertain. The present study endeavors to systematically analyze the effects of various dance forms on reducing the risk of falls among older adult, with the aim of providing evidence-based insights into the most efficacious dance styles for this population.DesignThe network meta-analysis of the existing literature was conducted to synthesize the available evidence regarding the effectiveness of various dance interventions in reducing the risk of falls among older adults.MethodsWe searched seven databases for randomized controlled trials on dance interventions for fall prevention in older adults and used Stata 17.0 for network meta-analysis.ResultsTwenty-seven studies (n = 1,219 older adults) were included. Creative Dance (CD) significantly improved the Berg Balance Scale score in healthy older adults (p < 0.05) and ranked best. Folk Dance (FD), CD, and Ballroom Dance (BD) all significantly improved Timed Up and Go time compared to controls, with FD ranking best overall. In Parkinson’s disease patients, both BD and FD significantly improved the Berg Balance Score, with FD again ranking best.ConclusionCreative dance, Folk dance, and Ballroom dance effectively reduce the risk of falls in older adults. Creative dance enhanced the Berg Balance Score the most among healthy older adults, while Folk dance improved the Timed Up and Go test performance the best. Similarly, among patients with Parkinson’s disease, Folk dance exhibits the best effect in improving Berg Balance Scale scores.Clinical trial registrationThe protocol of this study was registered with the International Prospective Register of Systematic Review, PROSPERO, under the identification number CRD42022323426, and can be integrally assessed online (https://www.crd.york.ac.uk/prospero/display_record.php?ID=CRD42022323426).